The Influence of Electronic Word of Mouth Toward Destination Trust and Travel Intention on Sirandah Island in Padang City - Okki Trinanda; Putra Deta Mutaqin (Komunitas Dosen Indonesia, 2019)
This research aims to analyze: (1) The influence of electronic word of mouth toward travel intention on Sirandah Island in Padang City (2) The influence of electronic word of mouth toward destination trust on Sirandah Island in Padang City (3) The influence of destination trust toward travel intention on Sirandah Island in Padang City. The type of this research is causative research. The population on this research is all Padang city society who have read online reviews of Sirandah Island in the internet and have never visited Sirandah Island whose numbers are unknwon. Data were collected through questionnaires and 170 questionnaires were analyzed by performing structural equation modeling (SEM) in SmartPLS 3.2.7. The result of this research show that (1) electronic word of mouth has a significant influenced on travel intention at Sirandah Island in Padang City (2) electronic word of mouth has a significant influenced on destination trust at Sirandah Island in Padang City (3) destination trust has a significant influenced on travel intention at Sirandah Island in Padang City